Effectiveness of ultrasonography-guided cardiac sympathetic denervation in acute control of electrical storm: A retrospective case series - Suheil Dhanse; Mugula Sudhakar Rao; Padmakumar Ramachandran; Tom Devasia; A J Ashwal; Ganesh Paramasivam; Manjunath Prabhu (Wolters Kluwer Medknow Publications, 2022)
Background and Aims: Ultrasonography-guided left cardiac sympathetic denervation (LCSD) or bilateral cardiac sympathetic denervation (BCSD) may be a useful intervention in the electrical storm (ES) that persists despite pharmacological therapy. The aim of our study was to evaluate the effectiveness of ultrasonography-guided LCSD or BCSD in the acute control of ES. We conducted a retrospective case series of patients who underwent ultrasonography-guided CSD for control of ES at a tertiary care hospital. Material and Methods: Data of all patients who underwent unilateral or bilateral CSD were collected from January 2017 to December 2019. Eleven patients with ES refractory to standard antiarrhythmic therapy underwent ultrasonography-guided pharmacological CSD (eight underwent LCSD and three underwent BCSD). Quantitative data was expressed as mean and median with interquartile range (IQR). Non-quantitative data was expressed in proportions. Results: Eleven patients underwent ultrasonography-guided pharmacological CSD (eight underwent LCSD and three underwent BCSD). Six of the eleven patients were female (54.5%). Ischemia was the underlying substrate in nine patients (81.8%). Five patients (46%) had complete resolution of ventricular tachycardia (VT) after CSD and one had 90% reduction in episodes of VT. The median follow-up duration was 8 months inter-quartile range IQR (7-18). One patient succumbed to heart failure and one patient was lost to follow up. The other patients had no further events and were well at last follow up. Conclusion: Ultrasonography-guided pharmacological CSD is effective in the acute control of ES. It is easily performed with equipment that is readily available and relatively safe in terms of immediate complications and is an ideal second-line intervention when ES persists despite drug therapy.